The BRAVA Initiative - Anacleto, Junia (Journal on Interactive Systems, 2013)
The Brazilian Visual Analytics Initiative, or BRAVA, aims at leveraging the collaborative research in the field of VA promoting the networking among Brazilian and Canadian researchers. Annual BRAVA Exploratory workshops are being proposed since 2012 to provide a forum for discussions on potential research collaborative projects among Brazilians and between Brazilian and Canadian research centres.